FREQUENCY OF OCULAR MANIFESTATIONS OF CHRONIC GRAFT VERSUS HOST DISEASE - Arain, Muhammad Aamir; Niazi, Muhammad Khizar Khizar; Khan, Muhammad Dawood; Ahmed, Parvez; Naz, Muhammad Afzal; Fayyaz, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: With the advancement of techniques for haematopoietic cell transplantation, the number of transplant survivors is increasing rapidly and so are the chances of chronic graft versus host disease (cGVHD). The ocular manifestations of this disease have not been explored in our local population. This study was conducted to determine the frequency of ocular complications in cases of cGVHD following successful bone marrow transplantation. Methods: Twelve diagnosed cases of cGVHD were evaluated from June 2008 to March 2009 and there ocular manifestations were noted especially the ocular surface disorders, using double staining method with fluorescein and rose-bengal. Results: Nine patients (75%) were having dry eyes, 7 (58.3%) with mebomian glands dysfunction, 4 (33%) with acute conjunctivitis, 2 (16.7%) with bilateral lacrimal canalicular occlusion, and 1 (8.3%) each of bilateral posterior subcapsular cataract, unilateral sterile corneal epithelial defect, anterior uveitis, retinal haemorrhages and disc oedema. Conclusion: The higher frequency of dry eyes along with other ocular manifestations in patients of cGVHD suggests the need of close ophthalmic monitoring in all such cases. Keywords: Dry eyes, chronic graft versus host disease, haematopoietic cell transplantation